ANALISIS KRIMINOLOGI TERHADAP USAHA PERDAGANGAN TANPA SURAT IZIN (STUDI KASUS PERIZINAN TOKO OBAT) - ASKARIAL SH., MH; DELPI SUSANTI (SISI LAIN REALITA, 2017)
Evaluation is the process of comparing the standard to the facts and analyzing the results. The extent to which the policy achieves its goals and objectives. To be better, public policy is the decision made by the State, especially the government as a strategy to realize the objectives of the State concerned, the service is a process of the activities of a person or group of people to provide assistance optimally to others requiring both requested and unsolicited. Drug Definitions are materials or alloys of materials including biological products used to influence or investigate physiological or pathological systems. The Drug Store is selling drugs without requiring the pharmacist to exist or without a doctor's prescription, while the pharmacy is a store that sells products that are under a doctor's prescription or pharmacist. Related to that through Article 4 of Regional Regulation No. 12 of 2008 on the Distribution of License Nuisance mention the ordinance for the maintenance of drug store permits. For the indicator the authors use the indicator of KEPMENPAN No. 64 Year 2004, the location of research that is writer fokuskan dikota pekanbaru with type of research that is descriptive quantitative.